Spatio-temporal dynamics of tuberculosis clusters in Indonesia - Dyah Wulan Sumekar Rengganis Wardani; Endro Prasetyo Wahono (Wolters Kluwer Medknow Publications, 2020)
Context: Stratification of social determinants leads to clustering of low socioeconomic communities, which then leads to spatio-temporal tuberculosis (TB) clusters. While previous studies have investigated spatio-temporal TB clusters, few have reported on the dynamics of them and the characteristics of social determinants.Aims: To investigate the spatio-temporal dynamics of TB clusters in Bandar Lampung, Indonesia, from 2015 to 2016, and to identify the characteristics of population density and percentage of poverty of the clusters.Settings and Design: A cross-sectional study was performed to analyze the spatio-temporal dynamics of TB clusters. The sample consisted of 705 TB patients (2015) and 1134 TB patients (2016), registered in 30 community health centers in Bandar Lampung, Indonesia Subjects and Methods: Geographical coordinates of the TB patients' residence were collected using Geographical Positioning System. Secondary data, consisting of population density and the percentage of poverty, were obtained from the subdistrict office in the region under investigation.Statistical Analysis: Data were analyzed with space-time permutation model using SaTScan software.Results: Spatio-temporal dynamics of TB clusters were found in 2015 and 2016, including the number of significant clusters, TB cases within the clusters, as well as locations and sizes of the clusters. All the clusters were found to have similar social determinant characteristics: medium-high population density and low-medium percentage of poverty.Conclusions: TB control programs in countries with a high TB burden and low social determinants should consider the spatio-temporal dynamics of the TB cluster and its social determinant characteristics for a better TB's intervention.